2017
DOI: 10.1007/s00344-017-9719-1
|View full text |Cite|
|
Sign up to set email alerts
|

Biochemical and Physicochemical Background of Mammalian Androgen Activity in Winter Wheat Exposed to Low Temperature

Abstract: development of wheat. The AN-induced changes in redox homeostasis seemed to be important for processes of acclimation to low temperature and generative induction. AN influenced hormonal balance in wheat and stimulated accumulation among other gibberellins and cytokinins. For example, in aerial part of plants, the content of GA 3 was increased by AN in 12 days of cold by about 30%, whereas the content of cis-zeatin was increased by 65%. AN was absorbed into plant membranes (Langmuir bath studies). The membrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 70 publications
0
21
0
Order By: Relevance
“…Interestingly, at 5 °C, GA3 content increased in both mutants. As for GA3, this compound was discovered in the fungus Gibberella fujikuroi (Hedden and Sponsel 2015), but later its occurrence was proven in plants, for example, Fagus sylvatica, Pinus pinaster, Malus hupehensis, and Triticum aestivum (Fernández et al 1997;Delatorre et al 2017;Mao et al 2017;Janeczko et al 2018). Mao et al (2017) even found that treatment of Malus hupehensis apple seedlings with brassinolide decreases GA3 content in comparison to untreated plants.…”
Section: Gibberellinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, at 5 °C, GA3 content increased in both mutants. As for GA3, this compound was discovered in the fungus Gibberella fujikuroi (Hedden and Sponsel 2015), but later its occurrence was proven in plants, for example, Fagus sylvatica, Pinus pinaster, Malus hupehensis, and Triticum aestivum (Fernández et al 1997;Delatorre et al 2017;Mao et al 2017;Janeczko et al 2018). Mao et al (2017) even found that treatment of Malus hupehensis apple seedlings with brassinolide decreases GA3 content in comparison to untreated plants.…”
Section: Gibberellinsmentioning
confidence: 99%
“…Among the results from the hormone analyses, the results for the ABA accumulation seem to be the most important, as they may explain the differences in frost tolerance between our tested genotypes. ABA is a well-known factor whose increase is correlated with low temperature-stress conditions (Welbaum et al 1997;Gusta et al 2005;Janeczko et al 2018) and is considered to be a hormone, which protects plants against freezing (Veisz et al 1996). An accumulation of higher amounts of ABA correlates with low temperature resistance in maize (Janowiak et al 2003).…”
Section: Frost Tolerancementioning
confidence: 99%
“…The androstenedione (AN) is another common sex hormone precursor in both sexes and takes charge of the biosynthesis of testosterone (Haring et al, 2012). New result demonstrated the effect of androstenedione (1 μM) on winter wheat exposed to low temperature (Janeczko et al, 2018). A key role for AN is to mitigate damages caused by freezing temperatures and enhance frost resistance in wheat.…”
Section: Epinephrine Releases the Inhibition Of Floweringmentioning
confidence: 99%
“…Moreover, there has been found an interaction between animal hormone and plant hormone in wheat. AN triggers an accelerated generative development of wheat via increasing GA 3 and cytokinins (Janeczko et al, 2018). The frost resistance increases in the process due to AN-induced changes in redox homeostasis.…”
Section: Epinephrine Releases the Inhibition Of Floweringmentioning
confidence: 99%
“…In order to reduce the damage to plants under FT stress, osmoregulatory substances such as soluble protein and soluble sugar accumulate in plant tissues to maintain the osmotic pressure of cells (Li et al 2013b). At the same time, when exposed to low temperature stress, the increase of reactive oxygen species in the plant may cause the changes in density and activity of antioxidant enzymes to reduce the damage of active oxygen to plants (Janeczko et al 2018).…”
Section: Introductionmentioning
confidence: 99%